The scientific production at Federal University of Ceará: bibliometrics considerations for the period from 2009 to 2018 - Araújo, Wánderson Cássio Oliveira; Andretta, Pedro Ivo Silveira; Inomata, Danielly Oliveira (Informação em Pauta, 2020)
Bibliometrics is characterized as a quantitative study to evaluate science. This research is a bibliometric study of the scientific production of articles from the Federal University of Ceará. The research used the Web of Science and Scopus databases for data collection with timeframe from 2009 to 2018. The results point to the growth of the choice of open access journals, the publications of the medical and technological area among the most cited and with the highest quantity of production and the annual expansion of indexed articles in the researched databases. The article suggests a set of new researches in order to expand the level of knowledge about scientific production in the researched university.